Dual specific STAT3/5 degraders effectively block acute myeloid leukemia and natural killer/T cell lymphoma - Pölöske, Daniel; Sorger, Helena; Schönbichler, Anna; Araujo, Elvin D.; Neubauer, Heidi A.; Orlova, Anna; Timonen, Sanna H.; Abdallah, Diaaeldin I.; Ianevski, Aleksandr; Kuusanmäki, Heikki; Surbek, Marta; Heyes, Elisabeth; et al. (HemaSphere, 2024)
The transcription factors STAT3, STAT5A, and STAT5B steer hematopoiesis and immunity, but their enhanced expression and activation promote acute myeloid leukemia (AML) or natural killer/T cell lymphoma (NKCL). Current therapeutic strategies focus on blocking upstream tyrosine kinases to inhibit STAT3/5, but these kinase blockers are not selective against STAT3/5 activation and frequent resistance causes relapse, emphasizing the need for targeted drugs. We evaluated the efficacy of JPX‐0700 and JPX‐0750 as dual STAT3/5 binding inhibitors promoting protein degradation. JPX‐0700/−0750 decreased the mRNA and protein levels of STAT3/5 targets involved in cancer survival, metabolism, and cell cycle progression, exhibiting nanomolar to low micromolar efficacy. They induced cell death and growth arrest in both AML/NKCL cell lines and primary AML patient blasts. We found that both AML/NKCL cells hijack STAT3/5 signaling through either upstream activating mutations in kinases, activating mutations in STAT3, mutational loss of negative STAT regulators, or genetic gains in anti‐apoptotic, pro‐proliferative, or epigenetic‐modifying STAT3/5 targets. This emphasizes a vicious cycle for proliferation and survival through STAT3/5. Both JPX‐0700/−0750 treatment reduced leukemic cell growth in human AML or NKCL xenograft mouse models significantly, being well tolerated by mice. Synergistic cell death was induced upon combinatorial use with approved chemotherapeutics in AML/NKCL cells.